The melting pot of the Malays as a majority group with three minority Muslim ethnic groups - The Indian Muslims, Chinese Muslims and Mirik people of Malaysia: an evaluation of ethnic changes - Abdullah @ Chuah Hock Leng, Osman (Society for Science and Education, United Kingdom, 2014)
This research is concerning the melting pot of three minority Muslim ethnic groups; namely the Indian Muslims, the Chinese Muslims and the Mirik people of Sarawak as well as the Malays as the majority group in Malaysia. The methodology makes use of the theory of assimilation and preservation of individual group identities in the dynamic changes of ethnic behaviours as applied to the USA in the 19th century. In Malaysia, a survey is conducted on the Indian Muslims, the Chinese Muslims and the Mirik people to find out the changes experienced by these three minority Muslim groups with regard to the Malays. The results show that Islam is a very important attribute of the Malays and it has the impact of pulling the minority Muslim groups into the ways of the Malays. When the Chinese, Indian and Mirik people embrace Islam, they acquire a common identity with the Malays. When they practise Islam, like performing the five daily prayers, fasting, paying alms and going on the pilgrimage, they are gradually integrating into the Malays’ way of life. They also have common festivals with the Malays after conversion and the men frequently go to the mosque for Friday prayer. Assimilation is also accelerated by intermarriage between the Chinese and Indian Muslims with the Malays. As the sole medium of instruction in schools and universities, the Malay language also helps the Chinese and Indian Muslims to blend into the Malay’s lifestyle. However, non-assimilation is also taking place when the Indian Muslims marry spouses from India and both the Chinese and Indian Muslims send their children to their ethnic schools and universities in Taiwan/China or India respectively to preserve their ethnicity. While the Mirik people have totally assimilated into the Malays’ way of life, for the Chinese and Indian Muslims, both assimilation and preservation of their individual identity are still taking place.